Cognitive enhancers: consumption of psychostimulants in medicine (2022)
Psychostimulants are drugs that can be used to improve cognitive performance by students and health care professionals. This trend might establish a public health issue. The purpose of this study is to describe the prevalence of psychostimulant use in medical students and resident doctors, and to identify consumption related risk factors. The study was conducted through a self-administered, anonymous online survey. 355 respondents were included, 27% (n = 96) were resident doctors, 70.4% (n = 250) students and 2.5% (n = 9) specialists. 17.4% (n = 62) opted for psychostimulant drugs of which modafinil was the most chosen. The most desired effect was to improve wakefulness 83.6% (n = 51). The average age for consumers was 27.31±3.08 (p = 0.033). The multivariate analysis revealed that the predictive variables with highest risk of consumption were: having read the package insert (OR = 5.2; p = 0.0001), previous use of benzodiazepines (OR = 3.75; p = 0.045) and having considered ethical its use (OR=1.03; p = 0.0001). According to literature, the prevalent use of psychostimulants by doctors under training in our population might be higher than other countries. This study is an important source of information for health authorities as it highlights unrestricted access and inappropriate use of psychostimulants.